Pengaruh Model Pembelajaran Mind Mapping Berbasis HOTS terhadap Motivasi dan Hasil Belajar Siswa - Abdul Hakim Ma’ruf; Mohamad Syafii; Arie Purwa Kusuma (Mosharafa: Jurnal Pendidikan Matematika, 2019)
AbstrakPenelitian ini bertujuan untuk mengetahui bagaimana pengaruh penerapan model pembelajaran Mind Mapping berbasis HOTS terhadap hasil belajar matematika dan motivasi belajar matematika siswa. Jenis Penelitian ini adalah penelitian kuantitatif dengan pendekatan quasi eksperiment. Populasi pada penelitian ini adalah semua siswa sekolah menengah atas kelas XI di Jakarta Timur, pada Tahun Akademik 2018/2019. Adapun populasi terjangkau diambil berdasarkan nilai UNBK pada tahun ajaran 2017/2018 dan didapatkan SMAN 105 Jakarta sebagai kategori tinggi, MAN 2 Jakarta sebagai kategori sedang dan SMA BUDHI WARMAN 2 Jakarta sebagai kategori rendah. Analisis data menggunakan uji-t dengan taraf signifikansi . Hasil pada penelitian ini adalah sebagai berikut: 1) Ada pengaruh motivasi belajar siswa pada pembelajaran matematika model Mind Mapping berbasisl HOTS pada hasil belajar matematika siswa. 2) Terdapat perbedaan motivasi belajar matematika siswa dengan model pembelajaran Mind Mapping berbasis HOTS dan model pembelajaran Mind Mapping tanpa bantuan soal HOTS. 3) Terdapat perbedaan hasil belajar matematika siswa dengan model pembelajaran Mind Mapping berbasis HOTS dan model pembelajaran Mind Mapping tanpa bantuan soal HOTS.Kata Kunci: Mind Mapping, HOTS, Hasil belajar, Motivasi.  The Effect of Using Mind Mapping Learning Model in Solving HOTS Based Questions on Motivation and Student Mathematics Learning OutcomesAbstractThe purpose of this study is to find out the influence of the application of based on HOTS Mind Mapping learning models on mathematics learning outcomes and students' learning mathematics motivation. This research is quantitative research with a quasi-experimental approach. The population in this study were all high school students of class XI in East Jakarta, in the Academic Year 2018/2019. The affordable population is taken based on the UNBK value in the 2017/2018 school year and obtained SMAN 105 Jakarta as a high category, MAN 2 Jakarta as a medium category and SMA BUDHI WARMAN 2 Jakarta as a low category. Data analysis used a t-test with a significance level of 0.05. The results of this study are as follows: 1) There is an influence on students' learning mathematics motivation based on HOTS Mind Mapping models on student mathematics learning outcomes. 2) There is a difference in students' motivation to learn mathematics based on HOTS Mind Mapping learning models and Mind Mapping learning models without the help of HOTS questions. 3) There are differences in students' mathematics learning outcomes based on HOTS Mind Mapping learning models and Mind Mapping learning models without the help of HOTS questions.Keywords: Mind Mapping, HOTS, Learning Outcomes, Motivation.